PENGARUH PERMAINAN ESTAFET PUZZLE TERHADAP KERJA SAMA ANAK KELOMPOK A TK IT IZZUDDIN PALEMBANG - Risti Melia; sri Sumarni; syafdaningsih syafar (FKIP Universitas sriwijaya, 2017)
This report aims to review the influence of puzzle estafet game toward children cooperation group a at kindergarten it izzuddin palembang, which includes 4 indicators: (1) interaction, (2) responsible, (3) mutual assistance, (4) contribute.The kind of research use is pre experiment with the design one shoot case study. Engineering the sample use is purposive sampling with samples were 20 children. Treatment done about 4 times and each performed posstest.Posstest used a in form of pieces of observation that shown in the form the test scores.Value on every posstest totaled divided 4 obtained the average 73,9. As the data is hypothesized is data that is in class lower limit value bsh intervals category that 63 .From the data analysis obtained value tcount = 2,53 ? value ttable = 1,73 With significant level of 5 percent and dk = (19) so that concluded there is influence estafet puzzle game against cooperation group a child kindergarten it izzuddin palembang. This could this be proved that in the initial conditions the average cooperation interpetasi developing a very good (bsb) as much as 50 % the children were 10 , the son of by interpretation developed as expected (bsh) of (20%) the children were 4 , then a interpretation getting started (mb) of (20%) the children were 4 , While children with interprestasi undeveloped (bb) of (10%) the children were 2 . So concluded there are significant influence estafet puzzle game against cooperation children